Salute - Jámbor, Imre (4D Journal of Landscape Architecture and Garden Art, 2009)
Mihály Mőcsényi, the eminent professor of landscape architecture, celebrated his 90th birthday on November 9th. His long and successful carrier always furthered the development of the practice and the education of Hungarian landscape architecture and enhanced its appreciation at both the national and International level.
Keywords: Mőcsényi; professor; landscape architecture; education